Simplified Y6‐Based Nonfullerene Acceptors: In‐Depth Study on Molecular Structure–Property Relation, Molecular Dynamics Simulation, and Charge Dynamics. Issue 10 (21st December 2022) - Yuk, Dohun; Jee, Min Hun; Koh, Chang Woo; Park, Won‐Woo; Ryu, Hwa Sook; Lee, Dongchan; Cho, Shinuk; Rasool, Shafket; Park, Sungnam; Kwon, Oh‐Hoon; Kim, Jin Young; Woo, Han Young
Abstract: Two new Y6 derivatives of symmetrical YBO‐2O and asymmetrical YBO‐FO nonfullerene acceptors (NFAs) are prepared with a simplified synthetic procedure by incorporating octyl and fluorine substituents onto the terminal 2‐(3‐oxo‐2, 3‐dihydro‐1H‐inden‐1‐ylidene)malononitrile (INCN) moiety. By moving the alkyl substituents on the Y6 core to the terminal INCN moiety, the lowest unoccupied molecular orbital of the YBO NFAs increases without decreasing solubility, resulting in high open‐circuit voltages of the devices. Molecular dynamics simulation shows that YBO‐2O/‐FO preferentially form core–core and terminal–terminal dimeric interactions, demonstrating their tighter packing structure and higher electron mobility than Y6, which is consistent with 2D grazing incidence X‐ray scattering and space charge limited current measurements. In blend films, the hole transfer (HT) from YBO‐2O/‐FO to the polymer donor PM6 is studied in detail by transient absorption spectroscopy, demonstrating efficient HT from YBO‐FO to PM6 with their suitable energy level alignment. Despite the simplified synthesis, YBO‐FO demonstrates photovoltaic performance similar to that of Y6, exhibiting a power conversion efficiency of 15.01%. Overall, this design strategy not only simplifies the synthetic procedures but also adjusts the electrical properties by modifying the intermolecular packing and energy level alignment, suggesting a novel simplified molecular design of Y6 derivatives. Abstract : Two acceptor–donor–acceptor‐type nonfullerene acceptors (NFAs) are prepared by moving the alkyl substituents on the Y6 core to the terminal A moiety. This design strategy significantly simplifies the synthetic process, increases the lowest unoccupied molecular orbital, and improves dimeric interactions of nonfullerene acceptor (NFA) molecules. The photoelectrical, molecular dynamics simulation, molecular packing, and charge dynamics are discussed in detail.